Optically absorptive anisotropic film, laminate, method for producing laminate, and image display device

The integration of a dichroic substance with an antioxidant in a light-absorbing anisotropic film, combined with a transparent resin layer, addresses the issue of light resistance in polarizing films, ensuring superior orientation and durability.

JP7602597B2Active Publication Date: 2024-12-18FUJIFILM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023178102
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2024-12-18
Estimated Expiration
2038-04-27

AI Technical Summary

Technical Problem

Conventional polarizing films using organic dyes as dichroic substances suffer from inferior light resistance due to photooxidation-induced decomposition, leading to poor orientation and performance degradation.

Method used

A light-absorbing anisotropic film containing a dichroic substance with an azo group and an antioxidant, such as hindered phenol or hindered amine, is used to maintain excellent orientation and improve light resistance, accompanied by a transparent resin layer to enhance these properties.

Benefits of technology

The film maintains high orientation and resistance to light-induced degradation, resulting in improved performance and durability of the laminate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602597000053
    Figure 0007602597000053
  • Figure 0007602597000054
    Figure 0007602597000054
  • Figure 0007602597000001
    Figure 0007602597000001
Patent Text Reader

Abstract

To provide a light absorption anisotropic film which maintains superior alignability of a dichroic material and provide good light resistance when used in a laminate, and to provide a laminate, a manufacturing method therefor, and an image display device using the same.SOLUTION: A light absorption anisotropic film is provided, containing dichroic materials having an azo group, and at least one type of antioxidant, where content of the antioxidant is 1-25 mol% with respect to the total molar mass of the dichroic materials, and at least one of the dichroic materials has a structure represented by a formula (1) below.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optically absorptive anisotropic film, a laminate, a method for producing the laminate, and an image display device. [Background technology]

[0002] In the past, when it was necessary to attenuate, polarize, scatter, or block irradiated light, including laser light or natural light, devices that operated on different principles for each function were used. Therefore, products that corresponded to the above functions were also manufactured using different manufacturing processes for each function. For example, in liquid crystal displays (LCDs), linear and circular polarizers are used to control the optical rotation and birefringence of the display, and in organic light emitting diodes (OLEDs), circular polarizers are also used to prevent reflection of external light.

[0003] In these polarizing plates (polarizing elements), iodine has been widely used as a dichroic material, but polarizing elements that use an organic dye as a dichroic material instead of iodine are also being considered. For example, Patent Document 1 describes a polarizing film formed from a composition containing a specific azo dye and a polymerizable liquid crystal compound ([Claim 1]). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-006502 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors have examined the polarizing film described in Patent Document 1 and found that it has excellent initial orientation of the azo dye (hereinafter simply referred to as "orientation"), but has clarified that it has poor light resistance depending on the layer structure of a laminate including the polarizing film.

[0006] Therefore, an object of the present invention is to provide an optically absorptive anisotropic film, a laminate, and a method for manufacturing the same, which can maintain excellent orientation of a dichroic material and improve light resistance when provided in a laminate, as well as an image display device using the same. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive research to achieve the above object, and have found that by providing a light absorbing anisotropic film containing a dichroic material having an azo group and an antioxidant, a laminate having good light resistance can be obtained while maintaining excellent orientation of the dichroic material, and have thus completed the present invention. That is, it has been found that the above object can be achieved by the following configuration.

[0008] [1] An optically absorptive anisotropic film containing a dichroic substance having an azo group and at least one type of antioxidant. [2] The optically absorptive anisotropic film according to [1], wherein the antioxidant comprises at least one of a hindered phenol, a hindered amine, a thioether, and a phosphite compound. [3] The optically absorptive anisotropic film according to [1] or [2], wherein the antioxidant is contained in an amount of 0.1 to 20% by mass based on the dichroic substance. [4] The optically absorptive anisotropic film according to any one of [1] to [3], wherein the dichroic substance having an azo group is a dichroic substance represented by the following formula (1): [ka] In formula (1), A 1 , A 2 and A 3 each independently represents a divalent aromatic group which may have a substituent. In formula (1), L1 and L 2 each independently represents a substituent. In formula (1), m represents an integer of 1 to 4. When m is an integer of 2 to 4, a plurality of A 2 may be the same or different from each other. [5] The optically absorptive anisotropic film according to any one of [1] to [4], wherein the dichroic substance has a structure represented by the following formula (2): [ka] In formula (2), A 4 represents a divalent aromatic group which may have a substituent. In formula (2), L 3 and L 4 each independently represents a substituent. In formula (2), E represents any one of a nitrogen atom, an oxygen atom, and a sulfur atom. In formula (2), R 1 represents a hydrogen atom, a halogen atom, an alkyl group which may have a substituent, or an alkoxy group which may have a substituent. In formula (2), R 2 represents a hydrogen atom or an alkyl group which may have a substituent. In formula (2), R 3 represents a hydrogen atom or a substituent. In formula (2), n represents 0 or 1. However, when E is a nitrogen atom, n is 1, and when E is an oxygen atom or a sulfur atom, n is 0. [6] In equation (2), A 4 The optically absorptive anisotropic film according to [5], wherein [7] In equation (2), L 3 and L 4 The optically absorptive anisotropic film according to [5] or [6], wherein at least one of the above contains a crosslinkable group. [8] In equation (2), L 3 and L 4 and wherein both of the above contain a crosslinkable group. [9] The optically absorptive anisotropic film according to [7] or [8], wherein the crosslinkable group is an acryloyl group or a methacryloyl group.

[10] The optically absorptive anisotropic film according to any one of [1] to [9], further comprising a liquid crystalline compound.

[11] A laminate comprising the optically absorptive anisotropic film according to any one of [1] to

[10] and a transparent resin layer, wherein the optically absorptive anisotropic film and the transparent resin layer are adjacent to each other.

[12] The laminate according to

[11] , wherein the transparent resin layer is a layer obtained using a curable composition containing at least one of a polymerizable compound and a polymer obtained by polymerizing the polymerizable compound.

[13] The laminate according to

[11] or

[12] , wherein the transparent resin layer further contains particles.

[14] The laminate according to any one of

[11] to

[13] , further comprising a transparent support on the opposite side to the transparent resin layer provided adjacent to the optically absorptive anisotropic film, and an alignment film between the transparent support and the optically absorptive anisotropic film.

[15] The alignment film is a photo-alignment film formed using a composition containing a photo-alignment compound, the photoalignment compound is a photosensitive compound having a photoreactive group that undergoes at least one of dimerization and isomerization by the action of light, The laminate according to

[14] , wherein the photoreactive group has a skeleton of at least one derivative or compound selected from the group consisting of cinnamic acid derivatives, coumarin derivatives, chalcone derivatives, maleimide derivatives, azobenzene compounds, polyimide compounds, stilbene compounds, and spiropyran compounds.

[16] The laminate according to any one of

[11] to

[15] , further comprising an adhesive layer on the opposite side of the transparent resin layer to the optically absorptive anisotropic film.

[17] The laminate according to

[16] , further comprising a λ / 4 plate on the side of the adhesive layer opposite to the transparent resin layer.

[18] A method for producing a laminate having an optically absorptive anisotropic film and a transparent resin layer, comprising the steps of: a light absorbing anisotropic film-forming step of forming a light absorbing anisotropic film using a composition containing a dichroic material represented by the following formula (1) and at least one antioxidant; A method for producing a laminate, comprising: a transparent resin layer forming step of forming a transparent resin layer on an optically absorptive anisotropic film using a curable composition containing at least one of a polymerizable compound and a polymer obtained by polymerizing the polymerizable compound. [ka] In formula (1), A 1 , A 2 and A 3 each independently represents a divalent aromatic group which may have a substituent. In formula (1), L 1 and L 2 each independently represents a substituent. In formula (1), m represents an integer of 1 to 4. When m is an integer of 2 to 4, a plurality of A 2 may be the same or different from each other.

[19] An image display device comprising the laminate according to any one of

[11] to

[17] and a display element provided on the opposite side of the transparent resin layer in the laminate to the optically absorptive anisotropic film side. Effect of the Invention

[0009] According to the present invention, it is possible to provide an optically absorptive anisotropic film, a laminate, and a method for manufacturing the same, which can maintain excellent orientation of a dichroic material and improve light resistance when provided in a laminate, as well as an image display device using the same. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the laminate of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of the laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. The following description of the components may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In this specification, "(meth)acrylic" is a general term for "acrylic" and "methacrylic", and "(meth)acrylate" is a general term for acrylate and methacrylate.

[0012] [Laminate] The laminate of the present invention is a laminate having an optically absorptive anisotropic film and a transparent resin layer. The optically absorptive anisotropic film in the laminate of the present invention is a film obtained by using a composition containing a dichroic material represented by formula (1) described below. The transparent resin layer of the laminate of the present invention is a layer obtained by using a curable composition containing particles and at least one of a polymerizable compound and a polymer obtained by polymerizing the polymerizable compound. Here, the term "transparent" in the present invention indicates that the transmittance of visible light is 60% or more, preferably 80% or more, and particularly preferably 90% or more.

[0013] In the present invention, as described above, by providing a light absorbing anisotropic film containing a dichroic material having an azo group and an antioxidant, it is possible to maintain excellent alignment of the dichroic material and form a laminate with good light resistance. Although the details of the reason for this are not yet clear, the present inventors speculate that it is due to the following reasons. First, the inventors investigated the cause of poor light resistance of conventionally known polarizing elements (polarizing films) that use organic dyes as dichroic materials, and found that the cause is decomposition of the dichroic materials by radicals generated in the photo-oxidation process. Therefore, in the present invention, it is believed that the light resistance is improved as a result of adding an antioxidant that is known to quench radicals in some cases. It was also found that the addition of an antioxidant to a conventionally known polarizing element (polarizing film) reduces the alignment of the dichroic material. Surprisingly, it was found that the use of the dichroic material and antioxidant discovered in the present invention can improve light resistance while maintaining the excellent alignment of the dichroic material. It is believed that the antioxidant promotes the crystallization of the dichroic material, resulting in increased anisotropy of the dichroic dye and excellent alignment. Furthermore, the present inventors have surprisingly found that the alignment and light resistance of the dichroic material can be further improved by providing a transparent resin layer on the optically absorptive anisotropic film, which is believed to be because the provision of the transparent resin layer suppresses the scattering and decomposition of the antioxidant.

[0014] 1 and 2 are schematic cross-sectional views showing an example of the laminate of the present invention. Here, the laminate 10 shown in FIG. 1 is a laminate having a layer structure (hereinafter also abbreviated as "structure 1") including a transparent support 12, an alignment film 14, an optically absorptive anisotropic film 16, and a transparent resin layer 18 in this order. Furthermore, the laminate 20 shown in FIG. 2 is a laminate having a layer structure (hereinafter also abbreviated as "structure 2") including a transparent support 12, an alignment film 14, an optically absorptive anisotropic film 16, a transparent resin layer 18 and an adhesive layer 19 in this order. In the examples of Figures 1 and 2, an embodiment is shown in which the laminate of the present invention has a transparent support and an alignment film, but this is not limited thereto, and the laminate of the present invention may not have at least one of the transparent support and the alignment film.

[0015] [Light-absorbing anisotropic film] The optically absorptive anisotropic film of the laminate of the present invention is a film obtained by using a composition containing a dichroic material. As the dichroic material, a dichroic material represented by the following formula (1) (hereinafter, also referred to as "specific dichroic material") is preferable. The optically absorptive anisotropic film may contain the dichroic substance itself, a polymer of the dichroic substance, or both.

[0016] [ka]

[0017] Here, in formula (1), A 1 , A 2 and A 3 each independently represents a divalent aromatic group which may have a substituent. In addition, in formula (1), L 1 and L 2 each independently represents a substituent. In addition, in formula (1), m represents an integer of 1 to 4. When m is an integer of 2 to 4, a plurality of A 2 may be the same or different. It is preferable that m is 1 or 2.

[0018] In the above formula (1), A 1 , A 2 and A 3 The "divalent aromatic group which may have a substituent" represented by the formula (I) will be explained below. Examples of the substituent include the substituent group G described in paragraphs

[0237] to

[0240] of JP 2011-237513 A. Among them, a halogen atom, an alkyl group, an alkoxy group, an alkoxycarbonyl group (e.g., methoxycarbonyl, ethoxycarbonyl, etc.), an aryloxycarbonyl group (e.g., phenoxycarbonyl, 4-methylphenoxycarbonyl, 4-methoxyphenylcarbonyl, etc.), etc. are preferred, an alkyl group is more preferred, and an alkyl group having 1 to 5 carbon atoms is particularly preferred. On the other hand, examples of the divalent aromatic group include a divalent aromatic hydrocarbon group and a divalent aromatic heterocyclic group. Examples of the divalent aromatic hydrocarbon group include arylene groups having 6 to 12 carbon atoms, specifically, phenylene groups, cumenylene groups, mesitylene groups, tolylene groups, xylylene groups, etc. Among these, the phenylene group is preferable. In addition, the divalent aromatic heterocyclic group is preferably a group derived from a monocyclic or bicyclic heterocycle. Examples of the atoms other than carbon constituting the aromatic heterocyclic group include a nitrogen atom, a sulfur atom, and an oxygen atom. When the aromatic heterocyclic group has a plurality of atoms constituting the ring other than carbon, these atoms may be the same or different. Specific examples of the aromatic heterocyclic group include a pyridylene group (pyridine-diyl group), a quinolylene group (quinoline-diyl group), an isoquinolylene group (isoquinoline-diyl group), a benzothiadiazole-diyl group, a phthalimide-diyl group, and a thienothiazole-diyl group (hereinafter, abbreviated as "thienothiazole group"). Among the above divalent aromatic groups, divalent aromatic hydrocarbon groups are preferred.

[0019] Here, A 1 , A 2 and A 3 It is preferable that any one of the above is a divalent thienothiazole group which may have a substituent. Specific examples of the substituent of the divalent thienothiazole group are the same as the substituent in the above-mentioned "divalent aromatic group which may have a substituent", and the preferred embodiments are also the same. Also, A 1 , A 2 and A 3 Of these, A 2 It is more preferable that A is a divalent thienothiazole group. 1 and A 2 represents a divalent aromatic group which may have a substituent. A 2 When A is a divalent thienothiazole group, 1 and A 2 At least one of A is preferably a divalent aromatic hydrocarbon group which may have a substituent. 1 and A 2 It is more preferable that both of the above are divalent aromatic hydrocarbon groups which may have a substituent.

[0020] In the above formula (1), L 1 and L 2The "substituent" represented by will be explained. The above-mentioned substituent is preferably a group introduced to enhance solubility or nematic liquid crystallinity, a group having electron-donating or electron-withdrawing properties introduced to adjust the color tone as a dye, or a group having a crosslinkable group (polymerizable group) introduced to fix the orientation. For example, the substituent may be an alkyl group (preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 12 carbon atoms, and particularly preferably an alkyl group having 1 to 8 carbon atoms, such as a methyl group, an ethyl group, an isopropyl group, a tert-butyl group, an n-octyl group, an n-decyl group, an n-hexadecyl group, a cyclopropyl group, a cyclopentyl group, or a cyclohexyl group), an alkenyl group (preferably an alkenyl group having 2 to 20 carbon atoms, more preferably an alkenyl group having 2 to 12 carbon atoms, and particularly preferably an alkenyl group having 2 to 8 carbon atoms, such as a vinyl group, an allyl group, or a 2-butenyl group). groups, and 3-pentenyl groups, etc.), alkynyl groups (preferably alkynyl groups having 2 to 20 carbon atoms, more preferably 2 to 12 carbon atoms, and particularly preferably 2 to 8 carbon atoms, such as a propargyl group and a 3-pentenyl group, etc.), aryl groups (preferably aryl groups having 6 to 30 carbon atoms, more preferably 6 to 20 carbon atoms, and particularly preferably 6 to 12 carbon atoms, such as a phenyl group, a 2,6-diethylphenyl group, a 3,5-ditrifluoromethylphenyl group, a styryl group, a naphthyl group, and a biphenyl group, etc. a substituted or unsubstituted amino group (preferably having 0 to 20 carbon atoms, more preferably having 0 to 10 carbon atoms, and particularly preferably having 0 to 6 carbon atoms; examples of which include an unsubstituted amino group, a methylamino group, a dimethylamino group, a diethylamino group, and an anilino group), an alkoxy group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 15 carbon atoms, and examples of which include a methoxy group, an ethoxy group, and a butoxy group), an oxycarbonyl group (preferably having 2 to 20 carbon atoms, more preferably having 2 to 15 carbon atoms, and particularly preferably having 2 to 6 carbon atoms). 10, for example, a methoxycarbonyl group, an ethoxycarbonyl group, a phenoxycarbonyl group, etc.), an acyloxy group (preferably having 2 to 20 carbon atoms, more preferably having 2 to 10 carbon atoms, particularly preferably having 2 to 6 carbon atoms, for example, an acetoxy group, a benzoyloxy group, an acryloyl group, etc.), an acylamino group (preferably having 2 to 20 carbon atoms, more preferably having 2 to 10 carbon atoms, particularly preferably having 2 to 6 carbon atoms, for example, an acetylamino group, a benzoylamino group, etc.),Alkoxycarbonylamino groups (preferably having 2 to 20 carbon atoms, more preferably having 2 to 10 carbon atoms, and particularly preferably having 2 to 6 carbon atoms; for example, methoxycarbonylamino groups, etc.), aryloxycarbonylamino groups (preferably having 7 to 20 carbon atoms, more preferably having 7 to 16 carbon atoms, and particularly preferably having 7 to 12 carbon atoms; for example, phenyloxycarbonylamino groups, etc.), sulfonylamino groups (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; for example, methanesulfonylamino groups, and a benzenesulfonylamino group), a sulfamoyl group (preferably having 0 to 20 carbon atoms, more preferably having 0 to 10 carbon atoms, and particularly preferably having 0 to 6 carbon atoms, such as a sulfamoyl group, a methylsulfamoyl group, a dimethylsulfamoyl group, and a phenylsulfamoyl group), a carbamoyl group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms, such as an unsubstituted carbamoyl group, a methylcarbamoyl group, a diethylcarbamoyl group, and a phenylcarbamoyl group). and the like), alkylthio groups (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples of such groups include a methylthio group and an ethylthio group), arylthio groups (preferably having 6 to 20 carbon atoms, more preferably having 6 to 16 carbon atoms, and particularly preferably having 6 to 12 carbon atoms; examples of such groups include a phenylthio group), sulfonyl groups (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples of such groups include a mesyl group and a tosyl group), sulfinyl groups (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples thereof include a methanesulfinyl group and a benzenesulfinyl group), ureido groups (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples thereof include an unsubstituted ureido group, a methylureido group, and a phenylureido group), phosphoramido groups (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples thereof include a diethyl phosphoramido group,and phenylphosphoramide groups, etc.), a hydroxy group, a mercapto group, a halogen atom (for example, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.), a cyano group, a nitro group, a hydroxamic acid group, a sulfino group, a hydrazino group, an imino group, an azo group, a heterocyclic group (preferably a heterocyclic group having 1 to 30 carbon atoms, more preferably a heterocyclic group having 1 to 12 carbon atoms, for example, a heterocyclic group having a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom, It is a ring group, for example, an epoxy group, an oxetanyl group, an imidazolyl group, a pyridyl group, a quinolyl group, a furyl group, a piperidyl group, a morpholino group, a benzoxazolyl group, a benzimidazolyl group, and a benzthiazolyl group, etc.), and a silyl group (preferably a silyl group having 3 to 40 carbon atoms, more preferably a silyl group having 3 to 30 carbon atoms, and particularly preferably a silyl group having 3 to 24 carbon atoms, for example, a trimethylsilyl group, a triphenylsilyl group, etc.). These substituents may be further substituted with other substituents. When there are two or more substituents, they may be the same or different. If possible, they may be bonded to each other to form a ring.

[0021] L 1 and L 2The substituent represented by is preferably an alkyl group which may have a substituent, an alkenyl group which may have a substituent, an alkynyl group which may have a substituent, an aryl group which may have a substituent, an alkoxy group which may have a substituent, an oxycarbonyl group which may have a substituent, an acyloxy group which may have a substituent, an acylamino group which may have a substituent, an amino group which may have a substituent, an alkoxycarbonylamino group which may have a substituent, a sulfonylamino group which may have a substituent, a sulfamoyl group which may have a substituent, a carbamoyl group which may have a substituent, an alkylthio group which may have a substituent, a sulfonyl group which may have a substituent, an ureido group which may have a substituent, a nitro group, a hydroxy group, a cyano group, an imino group, an azo group, a halogen atom, and a heterocyclic group, and more preferably an alkyl group which may have a substituent, an alkenyl group which may have a substituent, an aryl group which may have a substituent, an alkoxy group which may have a substituent, an oxycarbonyl group which may have a substituent, an acyloxy group which may have a substituent, an amino group which may have a substituent, a nitro group, an imino group, and an azo group.

[0022] L 1 and L 2 At least one of L 1 and L 2 It is more preferable that both of the above groups contain a crosslinkable group. Specific examples of the crosslinkable group include the polymerizable groups described in paragraphs

[0040] to

[0050] of JP2010-244038A. From the viewpoints of reactivity and synthetic suitability, an acryloyl group, a methacryloyl group, an epoxy group, an oxetanyl group, or a styryl group is preferable, and an acryloyl group or a methacryloyl group is more preferable.

[0023] L 1 and L 2Preferred embodiments of the above include an alkyl group substituted with the above crosslinkable group, a dialkylamino group substituted with the above crosslinkable group, and an alkoxy group substituted with the above crosslinkable group.

[0024] In the present invention, the specific dichroic substance preferably has a structure represented by the following formula (2) because this further improves the degree of orientation of the specific dichroic substance contained in the optically absorptive anisotropic film.

[0025] [ka]

[0026] Here, in formula (2), A 4 represents a divalent aromatic group which may have a substituent. In addition, in formula (2), L 3 and L 4 each independently represents a substituent. In addition, in formula (2), E represents any one of a nitrogen atom, an oxygen atom, and a sulfur atom. In addition, in formula (2), R 1 represents a hydrogen atom, a halogen atom, an alkyl group which may have a substituent, or an alkoxy group which may have a substituent. In addition, in formula (2), R 2 represents a hydrogen atom or an alkyl group which may have a substituent. In addition, in formula (2), R 3 represents a hydrogen atom or a substituent. In addition, in formula (2), n represents 0 or 1. However, when E is a nitrogen atom, n is 1, and when E is an oxygen atom or a sulfur atom, n is 0.

[0027] In the above formula (2), A 4 Specific examples and preferred embodiments of the "divalent aromatic group which may have a substituent" represented by A in the above formula (1) are 1 ~A 3 The above is the same as the "divalent aromatic group which may have a substituent" represented by the above formula (1). A 4A particularly preferred embodiment of is a phenylene group.

[0028] In the above formula (2), L 3 and L 4 Specific examples and preferred embodiments of the "substituent" represented by are L in the above formula (1). 1 and L 2 The substituent is the same as that represented by the above formula. L 3 and L 4 A preferred embodiment of the present invention is L 3 and L 4 In a more preferred embodiment, at least one of L 3 and L 4 In this case, the degree of orientation of the specific dichroic substance contained in the light absorption anisotropic film is improved, and the high temperature durability and the moist heat durability of the laminate are improved. Also, L 3 and L 4 A preferred embodiment of the crosslinkable group is an acryloyl group or a methacryloyl group.

[0029] In the above formula (2), E represents any one of a nitrogen atom, an oxygen atom, and a sulfur atom, and is preferably a nitrogen atom from the viewpoint of suitability for synthesis. Furthermore, from the viewpoint of facilitating the conversion of the specific dichroic substance to one having absorption on the short wavelength side (for example, one having a maximum absorption wavelength in the vicinity of 500 to 530 nm), E in the above formula (1) is preferably an oxygen atom. On the other hand, from the viewpoint of facilitating the conversion of the specific dichroic substance to one having absorption on the long wavelength side (for example, one having a maximum absorption wavelength around 600 nm), E in the above formula (1) is preferably a nitrogen atom.

[0030] In the above formula (2), R 1 represents a hydrogen atom, a halogen atom, an optionally substituted alkyl group or an optionally substituted alkoxy group, and is preferably a hydrogen atom or an optionally substituted alkyl group. Next, R 1The "optionally substituted alkyl group" and "optionally substituted alkoxy group" represented by the formula (I) will be explained below. Examples of the substituent include a halogen atom. The alkyl group may be a linear, branched, or cyclic alkyl group having 1 to 8 carbon atoms. Of these, a linear alkyl group having 1 to 6 carbon atoms is preferred, a linear alkyl group having 1 to 3 carbon atoms is more preferred, and a methyl group or an ethyl group is even more preferred. The alkoxy group includes an alkoxy group having 1 to 8 carbon atoms. Among them, an alkoxy group having 1 to 6 carbon atoms is preferable, an alkoxy group having 1 to 3 carbon atoms is more preferable, and a methoxy group or an ethoxy group is particularly preferable.

[0031] In the above formula (2), R 2 represents a hydrogen atom or an alkyl group which may have a substituent, and is preferably an alkyl group which may have a substituent. R 2 Specific examples and preferred embodiments of the "alkyl group which may have a substituent" represented by R 1 Since this is the same as the "alkyl group which may have a substituent" in the above, the explanation thereof will be omitted. In addition, R 2 is a group present in formula (2) when E is a nitrogen atom (i.e., n=1). On the other hand, R 2 When E is an oxygen atom or a sulfur atom, it is a group that does not exist in formula (2) (that is, it means the case where n=0).

[0032] In the above formula (2), R 3 represents a hydrogen atom or a substituent. R 3 Specific examples and preferred embodiments of the "substituent" represented by are the same as the substituents in the above-mentioned "divalent aromatic group which may have a substituent", and preferred embodiments are also the same, so description thereof will be omitted.

[0033] In the above formula (2), n represents 0 or 1. However, when E is a nitrogen atom, n is 1, and when E is an oxygen atom or a sulfur atom, n is 0.

[0034] Specific examples of the specific dichroic substance represented by the above formula (1) include the compounds described in paragraphs

[0051] to

[0081] of JP2010-152351A, the contents of which are incorporated herein by reference. Among these, as the specific dichroic substance having the structure represented by the above formula (2), in addition to the compounds (D-1) to (D-53) described in paragraphs

[0074] to

[0081] of JP2010-152351A, the following compounds (D-54) to (D-58) are also preferably mentioned.

[0035] Specific examples of the dichroic material are shown below, but the invention is not limited thereto. [ka]

[0036] [ka]

[0037] The content of the dichroic substance is preferably from 1 to 25 mass %, particularly preferably from 5 to 20 mass %, based on the total mass of all solid contents in the composition. In the present invention, it is preferable that the optically absorptive anisotropic film is a film formed using a composition containing the above-mentioned dichroic substance and a liquid crystalline compound (hereinafter also referred to as a "liquid crystal composition"), because this makes it possible to align the dichroic substance with a higher degree of orientation while suppressing precipitation of the dichroic substance.

[0038] <Liquid crystal compounds> As the liquid crystal compound contained in the liquid crystal composition, either a low molecular weight liquid crystal compound or a high molecular weight liquid crystal compound can be used. Here, the term "low molecular weight liquid crystal compound" refers to a liquid crystal compound that does not have a repeating unit in its chemical structure. Moreover, the term "polymeric liquid crystal compound" refers to a liquid crystal compound having a repeating unit in the chemical structure. Examples of low molecular weight liquid crystal compounds include those described in JP-A-2013-228706. Examples of the polymer liquid crystal compound include the thermotropic liquid crystal polymers described in JP 2011-237513 A. The polymer liquid crystal compound may have a crosslinkable group (e.g., an acryloyl group or a methacryloyl group) at the end.

[0039] <Interfacial improver> The liquid crystal composition preferably contains an interfacial modifier. By containing the interfacial modifier, the smoothness of the coating surface is improved, and the degree of orientation is improved, and repelling and unevenness are suppressed, thereby improving the in-plane uniformity. The interface improver is preferably one that makes the liquid crystal compound horizontal on the coating surface side, and the compounds (horizontal alignment agents) described in paragraphs

[0253] to

[0293] of JP2011-237513A can be used. When the liquid crystal composition contains an interface modifier, the content of the interface modifier is preferably 0.001 to 5 parts by mass, and more preferably 0.01 to 3 parts by mass, per 100 parts by mass of the total of the dichroic substance and the liquid crystal compound in the liquid crystal composition.

[0040] <Polymerization initiator> The liquid crystal composition may contain a polymerization initiator. The polymerization initiator is not particularly limited, but is preferably a compound having photosensitivity, that is, a photopolymerization initiator. As the photopolymerization initiator, various compounds can be used without any particular limitation. Examples of the photopolymerization initiator include α-carbonyl compounds (U.S. Pat. Nos. 2,367,661 and 2,367,670), acyloin ethers (U.S. Pat. No. 2,448,828), α-hydrocarbon-substituted aromatic acyloin compounds (U.S. Pat. No. 2,722,512), polynuclear quinone compounds (U.S. Pat. Nos. 3,046,127 and 2,951,758), and combinations of triaryl imidazole dimers and p-aminophenyl ketones. Examples of such compounds include compounds (U.S. Pat. No. 3,549,367), acridine and phenazine compounds (Japanese Patent Laid-Open No. 60-105667 and U.S. Pat. No. 4,239,850), oxadiazole compounds (U.S. Pat. No. 4,212,970), and acylphosphine oxide compounds (Japanese Patent Publication No. 63-40799, Japanese Patent Publication No. 5-29234, Japanese Patent Laid-Open No. 10-95788 and Japanese Patent Laid-Open No. 10-29997). As such a photopolymerization initiator, commercially available products can be used, such as Irgacure 184, Irgacure 907, Irgacure 369, Irgacure 651, Irgacure 819, and Irgacure OXE-01 manufactured by BASF. When the liquid crystal composition of the present invention contains a polymerization initiator, the content of the polymerization initiator is preferably 0.01 to 30 parts by mass, and more preferably 0.1 to 15 parts by mass, relative to 100 parts by mass of the total of the dichroic substance and the liquid crystal compound in the liquid crystal composition. When the content of the polymerization initiator is 0.01 part by mass or more, the curability of the optically absorptive anisotropic film becomes good, and when it is 30 parts by mass or less, the alignment of the optically absorptive anisotropic film becomes good.

[0041] <Antioxidants> Any known antioxidant can be used without any particular restrictions. Examples are described in "Comprehensive Technology of Polymer Stabilization - Mechanism and Application Development" edited by Yasukazu Ohkatsu, published by CMC. Types of antioxidants include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. Furthermore, it is preferable to use a phenol-based antioxidant or an amine-based antioxidant in combination with a phosphorus-based antioxidant or a sulfur-based antioxidant.

[0042] Examples of the phenol-based antioxidants include Adeka STAB AO-20, AO-30, AO-40, AO-50, AO-60, AO-80, and AO-330 (manufactured by ADEKA Corporation), IRGANOX 1010, 1035, 1076, 1098, 1135, 1330, 1726, 245, 259, 3114, and 565 (manufactured by BASF Corporation).

[0043] Examples of the amine-based antioxidants include Sanol LS-770, Sanol LS-765, Sanol LS-2626 (manufactured by Sankyo Co., Ltd.), Adeka STAB LA-77, LA-57, LA-52, LA-62, LA-63, LA-67, LA-68, LA-72 (manufactured by ADEKA Corporation), TINUVIN 123, TINUVIN 144, TINUVIN 622, TINUVIN 765, TINUVIN 944 (manufactured by Ciba Specialty Chemicals Corporation). In the present invention, an amine-based compound capable of quenching radicals can also be used, such as polyethylene glycol bis-TEMPO (manufactured by Aldrich) and sebacate bis-TEMPO.

[0044] Examples of phosphorus-based antioxidants include Adeka STAB PEP-8, PEP-36, HP-10, 2112 (manufactured by ADEKA Corporation), and IRGAFOS168 (manufactured by BASF Corporation).

[0045] Examples of the sulfur-based antioxidant include Adeka STAB AO-412S and AO-503S (manufactured by ADEKA Corporation).

[0046] From the viewpoint of the orientation of the dichroic material, the antioxidant preferably has an L / D (L: length, D: width) of the orienting molecule of 1.2 or more.

[0047] The content of the antioxidant is preferably 1 to 25 mol %, particularly preferably 5 to 20 mol %, based on the total molar mass of the dichroic material. The higher the content, the more the decomposition of the dichroic material due to photooxidation can be suppressed, but the above content is preferable because it is easy to achieve compatibility with the orientation of the dichroic material.

[0048] <Solvent> From the viewpoint of workability and the like, the liquid crystal composition preferably contains a solvent. Examples of the solvent include ketones (e.g., acetone, 2-butanone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, etc.), ethers (e.g., dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (e.g., hexane, etc.), alicyclic hydrocarbons (e.g., cyclohexane, etc.), aromatic hydrocarbons (e.g., benzene, toluene, xylene, trimethylbenzene, etc.), and halogenated carbons (e.g., dichloromethane, trichloromethane, dichloroethane, dichlorobenzene, chlorotoluene, etc.). Examples of the organic solvent include organic solvents such as esters (e.g., methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (e.g., ethanol, isopropanol, butanol, cyclohexanol, etc.), cellosolves (e.g., methyl cellosolve, ethyl cellosolve, 1,2-dimethoxyethane, etc.), cellosolve acetates, sulfoxides (e.g., dimethyl sulfoxide, etc.), amides (e.g., dimethylformamide, dimethylacetamide, etc.), and heterocyclic compounds (e.g., pyridine, etc.), as well as water. These solvents may be used alone or in combination of two or more. Of these solvents, it is preferable to use an organic solvent, and it is more preferable to use a halogenated carbon or a ketone. When the liquid crystal composition contains a solvent, the content of the solvent is preferably 80 to 99 mass %, more preferably 83 to 97 mass %, and further preferably 85 to 95 mass %, relative to the total mass of the liquid crystal composition.

[0049] <Other ingredients> The liquid crystal composition may further contain a dichroic substance other than the specific dichroic substance, or may contain a plurality of the specific dichroic substances. When a plurality of dichroic substances are contained, from the viewpoint of further curing the liquid crystal composition, it is preferable to contain a dichroic substance having a crosslinkable group that crosslinks with the specific dichroic substance, and it is more preferable to contain a plurality of the specific dichroic substances.

[0050] <Formation method> The method for forming an optically absorptive anisotropic film using the above-mentioned liquid crystalline composition is not particularly limited, and examples thereof include a method including, in this order, a step of applying the above-mentioned liquid crystalline composition onto a transparent support described below to form a coating film (hereinafter also referred to as a "coating film forming step") and a step of orienting the liquid crystalline component contained in the coating film (hereinafter also referred to as an "orientation step"). The liquid crystal component is a component including not only the above-mentioned liquid crystal compound but also a dichroic substance having liquid crystallinity when the above-mentioned dichroic substance has liquid crystallinity.

[0051] (Coating film formation process) The coating film forming step is a step of coating a liquid crystalline composition on a transparent support to form a coating film. By using a liquid crystalline composition containing the above-mentioned solvent, or by using a liquid crystalline composition that has been made into a liquid such as a molten liquid by heating or the like, it becomes easy to apply the liquid crystalline composition onto a transparent support. Specific examples of the method for applying the liquid crystalline composition include known methods such as roll coating, gravure printing, spin coating, wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spraying, and ink jet methods. In this embodiment, the liquid crystal composition is applied onto a transparent support, but the present invention is not limited thereto, and the liquid crystal composition may be applied onto an alignment film provided on a transparent support. Details of the alignment film will be described later.

[0052] (Orientation process) The alignment step is a step for aligning the liquid crystal component contained in the coating film, thereby obtaining a light absorbing anisotropic film. The orientation step may include a drying treatment. By the drying treatment, components such as a solvent can be removed from the coating film. The drying treatment may be performed by leaving the coating film at room temperature for a predetermined time (for example, natural drying), or may be performed by heating and / or blowing air. Here, the liquid crystal component contained in the liquid crystal composition may be aligned by the above-mentioned coating film forming process or drying treatment. For example, in an embodiment in which the liquid crystal composition is prepared as a coating liquid containing a solvent, the coating film is dried to remove the solvent from the coating film, thereby obtaining a coating film having optical absorption anisotropy (i.e., an optical absorption anisotropic film). When the drying treatment is carried out at a temperature equal to or higher than the transition temperature of the liquid crystal component contained in the coating film to a liquid crystal phase, the heating treatment described below does not need to be carried out.

[0053] The transition temperature of the liquid crystal component contained in the coating film to the liquid crystal phase is preferably 10 to 250°C, more preferably 25 to 190°C, from the viewpoint of manufacturability, etc. If the transition temperature is 10°C or higher, cooling treatment or the like is not required to lower the temperature to the temperature range in which the liquid crystal phase is exhibited, which is preferable. In addition, if the transition temperature is 250°C or lower, a high temperature is not required even when the film is once in an isotropic liquid state at a temperature higher than the temperature range in which the liquid crystal phase is exhibited, which is preferable, since waste of thermal energy and deformation and deterioration of the substrate can be reduced.

[0054] The alignment step preferably includes a heat treatment, which allows the liquid crystal component contained in the coating film to be aligned, so that the coating film after the heat treatment can be suitably used as an optically absorptive anisotropic film. From the viewpoint of manufacturability, the heat treatment temperature is preferably from 10 to 250° C., more preferably from 25 to 190° C. The heating time is preferably from 1 to 300 seconds, more preferably from 1 to 60 seconds.

[0055] The alignment step may include a cooling treatment carried out after the heating treatment. The cooling treatment is a treatment for cooling the coated film after heating to about room temperature (20 to 25°C). This makes it possible to fix the alignment of the liquid crystal component contained in the coated film. The cooling means is not particularly limited and can be carried out by a known method. By the above steps, an optically absorptive anisotropic film can be obtained. In this embodiment, the method for aligning the liquid crystal component contained in the coating film includes drying treatment and heat treatment, but is not limited thereto and can be carried out by any known alignment treatment.

[0056] (Other processes) The method for producing the laminate may include a step of curing the optically absorptive anisotropic film (hereinafter also referred to as a "curing step") after the above-mentioned alignment step. The curing step is carried out, for example, by heating and / or light irradiation (exposure) when the optically absorptive anisotropic film has a crosslinkable group (polymerizable group). Among these, the curing step is preferably carried out by light irradiation. The light source used for curing can be various light sources such as infrared light, visible light, or ultraviolet light, but ultraviolet light is preferable. In addition, ultraviolet light may be irradiated while heating during curing, or ultraviolet light may be irradiated through a filter that transmits only specific wavelengths. When the exposure is performed with heating, the heating temperature during exposure is preferably 25 to 140° C., although it depends on the transition temperature to a liquid crystal phase of the liquid crystalline component contained in the light absorptive anisotropic film. The exposure may be carried out under a nitrogen atmosphere. When the curing of the optically absorptive anisotropic film proceeds by radical polymerization, it is preferable to carry out the exposure under a nitrogen atmosphere, since this reduces inhibition of polymerization caused by oxygen.

[0057] In the present invention, the thickness of the optically absorptive anisotropic film is not particularly limited, but is preferably 0.1 to 5.0 μm, and more preferably 0.3 to 1.5 μm.

[0058] The average refractive index of the optically absorptive anisotropic film at a wavelength of 550 nm is preferably from 1.45 to 2.50, and more preferably from 1.50 to 1.90. In this specification, the average refractive index (n ave ) is represented by the following formula (R1). Formula (R1) n ave =(n x +n y +n z ) / 3 In formula (R1), the direction in the plane where the refractive index is maximum is the x-axis, the direction perpendicular to this is the y-axis, and the normal direction to the plane is the z-axis. The respective refractive indices are n x , n y , n z Each refractive index is measured using a Woollam M-2000U spectroscopic ellipsometer.

[0059] [Transparent resin layer] The transparent resin layer of the laminate of the present invention is a layer obtained by using a curable composition containing at least one of a polymerizable compound and a polymer obtained by polymerizing the polymerizable compound. Furthermore, the transparent resin layer preferably contains inorganic particles. The transparent resin layer contains a polymerizable compound itself, contains a polymer obtained by polymerizing a polymerizable compound (hereinafter also simply referred to as a "polymer"), or contains both a polymerizable compound and a polymer.

[0060] <Particle> The particles include organic particles, inorganic particles, and organic-inorganic composite particles containing an organic component and an inorganic component. Examples of organic particles include styrene resin particles, styrene-divinylbenzene copolymer particles, acrylic resin particles, methacrylic resin particles, styrene-acrylic copolymer particles, styrene-methacrylic copolymer particles, melamine resin particles, and resin particles containing two or more of these. Specific examples of inorganic particles include inorganic oxide particles such as alumina particles, alumina hydrate particles, silica particles, zirconia particles, and clay minerals (eg, smectite). Examples of the organic-inorganic composite particles include core-shell particles containing, as an organic component, the resin constituting the organic particles, and, as an inorganic component, the inorganic oxide constituting the inorganic particles. Among the above, inorganic particles are preferred, inorganic oxide particles are more preferred, silica particles, alumina particles or alumina hydrate particles are even more preferred, and silica particles are particularly preferred, in that they provide a laminate with superior high temperature durability and moist heat durability. The particles may be used alone or in combination of two or more kinds.

[0061] The average particle size of the particles is preferably 1 to 300 nm, more preferably 10 to 200 nm, and particularly preferably 5 to 100 nm. Within the above range, the particles have excellent dispersibility, and a cured product (transparent resin layer) having excellent high temperature durability, moist heat durability, and transparency can be obtained. Here, the average particle size of the particles can be determined from a photograph obtained by observation with a TEM (transmission electron microscope) or SEM (scanning electron microscope). Specifically, the projected area of ​​the particles is determined, and the corresponding circle-equivalent diameter (diameter of a circle) is defined as the average particle size of the particles. Note that the average particle size in the present invention is the arithmetic mean value of the circle-equivalent diameters determined for 100 particles. For the TEM, a device equivalent to the transmission electron microscope "JEM-2010HC" (product name, manufactured by JEOL Ltd.) can be used. For the SEM, a device equivalent to the ultra-high resolution field emission scanning electron microscope "SU8010" (product name, manufactured by Hitachi High-Technologies Corporation) can be used. In addition, when using commercially available products as particles, the catalog value is preferentially adopted as the average particle size of the particles. In this case, the average particle size of the particles is preferably a number average particle size measured based on a dynamic light scattering method. Specifically, a mixture or dispersion containing particles is diluted with an arbitrary solvent, and the obtained diluted solution is measured using a dynamic light scattering method. For this measurement, it is preferable to use Microtrack UPA-EX150 manufactured by Nikkiso Co., Ltd.

[0062] The particles may be in any shape, such as spherical, needle-like, fibrous, columnar or plate-like, but from the viewpoint of superior light resistance of the laminate, spherical shapes that can be densely packed in the film are preferred.

[0063] The particles may be added to the curable composition in the form of a colloidal liquid dispersed in a solvent (at least one of water and an organic solvent). As the colloidal liquid, commercially available products can be used, for example, alumina sols such as AS-200 and AS-520-A (all manufactured by Nissan Chemical Industries, Ltd.), 10A, 10D, 10C, F-3000, CSA-110AD, A2, F-1000, and A2K5-10 (all manufactured by Kawaken Fine Chemicals Co., Ltd.), MEK-ST-40, MEK-ST-L, MEK-ST-ZL, MEK-ST-UP, and M Examples of silica sols include IBK-ST, MIBK-ST-L, CHO-ST-M, EAC-ST, PMA-ST, TOL-ST, MEK-AC-2140Z, MEK-AC-4130Y, MEK-AC-5140Z, PGM-AC-2140Y, PGM-AC-4130Y, MIBK-AC-2140Z, MIBK-SD-L, and MEK-EC-2130Y (all manufactured by Nissan Chemical Industries, Ltd.).

[0064] The content of the particles is preferably from 0 to 90 mass %, more preferably from 30 to 85 mass %, based on the total mass of all solid contents in the curable composition.

[0065] <Polymerizable compounds and polymers> The polymerizable compound means a compound that has a polymerizable group and can form a polymer by polymerization. The polymerizable compound may be a monofunctional polymerizable compound having one polymerizable group in one molecule, or a polyfunctional polymerizable compound having two or more identical or different polymerizable groups in one molecule. The polymerizable compound may be a monomer or a polymer such as an oligomer or a prepolymer. The polymerizable group may be a radical polymerizable group or a cationic polymerizable group, with the radical polymerizable group being preferred. The radical polymerizable group may be an ethylenically unsaturated bond group or the like. The cationic polymerizable group may be an epoxy group or an oxetane group or the like. Examples of the ethylenically unsaturated bond group include an acryloyl group, a methacryloyl group, a vinyl group, a styryl group, and an allyl group, with an acryloyl group and a methacryloyl group being preferred.

[0066] Specific examples of the polymerizable compound include the compounds described in paragraphs 0051 to 0059 of JP-A No. 2016-150537 and the compounds described in paragraphs 0046 to 0072 of JP-A No. 2016-056341. Specific examples include compounds represented by the following formulas, and among these, 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate represented by CEL2021P below is preferred. [ka] JPEG0007602597000009.jpg21133

[0067] Examples of the polymerizable compound having a hydrophilic group include KAYARAD PET-30 manufactured by Nippon Kayaku Co., Ltd. and polyfunctional acrylamide FAM-401 (manufactured by Fujifilm Corporation).

[0068] The total content of the polymerizable compound and the polymer is preferably 30% by mass or more, more preferably 40% by mass or more, particularly preferably 50 to 98% by mass, based on the total mass of all solid contents in the polymerizable composition.

[0069] <Polymerization initiator> The transparent resin forming composition may contain a polymerization initiator. The polymerization initiator is not particularly limited, but is preferably a compound having photosensitivity, that is, a photoradical polymerization initiator or a photocationic polymerization initiator (photoacid generator). Examples of the photoradical polymerization initiator include the same ones as those explained in the above-mentioned liquid crystal composition.

[0070] <<<Cationic Polymerization Initiator>>> The cationic polymerization initiator is preferably a cationic photopolymerization initiator. The cationic photopolymerization initiator may be any one that can generate cations as active species by irradiation with light, and known cationic photopolymerization initiators can be used without any restrictions. Specific examples include known sulfonium salts, ammonium salts, iodonium salts (e.g., diaryliodonium salts), triarylsulfonium salts, diazonium salts, and iminium salts. More specifically, examples include cationic photopolymerization initiators represented by formulas (25) to (28) shown in paragraphs 0050 to 0053 of JP-A-8-143806, and those exemplified as cationic polymerization catalysts in paragraph 0020 of JP-A-8-283320, the contents of which are incorporated herein by reference. In addition, the cationic photopolymerization initiator can be synthesized by a known method, and is also available as a commercially available product. Examples of commercially available products include CI-1370, CI-2064, CI-2397, CI-2624, CI-2639, CI-2734, CI-2758, CI-2823, CI-2855, and CI-5102 manufactured by Nippon Soda Co., Ltd., PHOTOINITIATOR 2047 manufactured by Rhodia, UVI-6974 and UVI-6990 manufactured by Union Carbide Corporation, and CPI-10P manufactured by San-Apro Ltd.

[0071] As the cationic photopolymerization initiator, diazonium salts, iodonium salts, sulfonium salts, and iminium salts are preferred from the viewpoints of the sensitivity of the photopolymerization initiator to light, the stability of the compound, etc. Also, from the viewpoint of weather resistance, iodonium salts are most preferred.

[0072] Specific examples of commercially available iodonium salt-based cationic photopolymerization initiators include B2380 manufactured by Tokyo Chemical Industry Co., Ltd., BBI-102 manufactured by Midori Chemical Industry Co., Ltd., WPI-113 manufactured by Wako Pure Chemical Industries, Ltd., WPI-124 manufactured by Wako Pure Chemical Industries, Ltd., WPI-169 manufactured by Wako Pure Chemical Industries, Ltd., WPI-170 manufactured by Wako Pure Chemical Industries, Ltd., and DTBPI-PFBS manufactured by Toyo Gosei Chemical Co., Ltd.

[0073] Specific examples of iodonium salt compounds that can be used as cationic photopolymerization initiators include the following compounds PAG-1 and PAG-2.

[0074] [ka]

[0075] [ka]

[0076] <Solvent> In addition to the hydrophilic monomer, the curable composition preferably contains a solvent from the viewpoint of workability and the like. As the solvent, the same solvents as those explained in the above-mentioned liquid crystal composition can be used.

[0077] <Formation method> The transparent resin layer can be formed, for example, by applying the above-mentioned curable composition onto the above-mentioned optically absorptive anisotropic film, drying the composition, and then polymerizing the composition to fix the composition. Here, the coating method is not particularly limited, and examples thereof include dip coating, air knife coating, curtain coating, roller coating, die coating, wire bar coating, and gravure coating. Here, the polymerization conditions are not particularly limited, but in the polymerization by light irradiation, it is preferable to use ultraviolet light. The irradiation amount is 10 mJ / cm 2 ~50J / cm 2 and preferably 20 mJ / cm2 ~5J / cm 2 More preferably, 30 mJ / cm 2 ~3J / cm 2 More preferably, the intensity is 50 to 1000 mJ / cm 2 In order to promote the polymerization reaction, the reaction may be carried out under heating conditions.

[0078] The thickness of the transparent resin layer is not particularly limited, but is preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm.

[0079] [Transparent support] The laminate of the present invention may have a transparent support on the side of the optically absorptive anisotropic film opposite to the transparent resin layer. Examples of materials for forming a transparent support include polycarbonate-based polymers; polyester-based polymers such as polyethylene terephthalate (PET) and polyethylene naphthalate; acrylic-based polymers such as polymethyl methacrylate; styrene-based polymers such as polystyrene and acrylonitrile-styrene copolymers (AS resins); polyolefin-based polymers such as polyethylene, polypropylene, and ethylene-propylene copolymers; vinyl chloride-based polymers; amide-based polymers such as nylon and aromatic polyamide; imide-based polymers; sulfone-based polymers; polyethersulfone-based polymers; polyetheretherketone-based polymers; polyphenylene sulfide-based polymers; vinylidene chloride-based polymers; vinyl alcohol-based polymers; vinyl butyral-based polymers; arylate-based polymers; polyoxymethylene-based polymers; epoxy-based polymers; and the like.

[0080] As a material for forming the transparent support, a thermoplastic norbornene-based resin can be preferably used. Examples of such a thermoplastic norbornene-based resin include Zeonex and Zeonor manufactured by Zeon Corporation, and Arton manufactured by JSR Corporation. As a material for forming a transparent support, a cellulose-based polymer, typically triacetyl cellulose (TAC), can also be preferably used.

[0081] In the present invention, the thickness of the transparent support is not particularly limited, and is preferably 100 μm or less, more preferably 80 μm or less, and further preferably 10 to 80 μm.

[0082] [Alignment film] The laminate of the present invention may have an alignment film between the transparent support and the optically absorptive anisotropic film. Methods for forming an alignment film include, for example, rubbing an organic compound (preferably a polymer) onto the film surface, oblique deposition of an inorganic compound, formation of a layer having microgrooves, and accumulation of an organic compound (e.g., ω-tricosanoic acid, dioctadecylmethylammonium chloride, methyl stearyl acid, etc.) by the Langmuir-Blodgett method (LB film), etc. Furthermore, alignment films that exhibit alignment function by application of an electric field, a magnetic field, or light irradiation are also known. Among these, in the present invention, an alignment film formed by a rubbing treatment is preferred from the viewpoint of ease of control of the pretilt angle of the alignment film, and a photo-alignment film formed by light irradiation is also preferred from the viewpoint of uniformity of alignment.

[0083] <Rubbed alignment film> Polymer materials used for the alignment film formed by rubbing treatment are described in many documents, and many commercial products are available. In the present invention, polyvinyl alcohol or polyimide and its derivatives are preferably used. For the alignment film, reference can be made to the description on page 43, line 24 to page 49, line 8 of International Publication WO01 / 88574A1. The thickness of the alignment film is preferably 0.01 to 10 μm, and more preferably 0.01 to 1 μm.

[0084] <Photo-alignment film> Photo-alignment compounds used in alignment films formed by light irradiation are described in many documents. In the present invention, for example, azo compounds described in JP-A-2006-285197, JP-A-2007-76839, JP-A-2007-138138, JP-A-2007-94071, JP-A-2007-121721, JP-A-2007-140465, JP-A-2007-156439, JP-A-2007-133184, JP-A-2009-109831, Japanese Patent No. 3883848, and Japanese Patent No. 4151746, and azo compounds described in JP-A-2002-229039 are used. Preferred examples include the aromatic ester compounds described above, maleimide and / or alkenyl-substituted nadimide compounds having a photo-orientable unit described in JP-A-2002-265541 and JP-A-2002-317013, photo-crosslinkable silane derivatives described in JP-A-2003-520878 and JP-A-2004-529220, and photo-crosslinkable polyimides, polyamides, or esters described in JP-A-2003-520878, JP-A-2004-529220, or JP-A-2004-529220. More preferred are azo compounds, photo-crosslinkable polyimides, polyamides, or esters.

[0085] Of these, it is preferable to use, as the photoalignment compound, a photosensitive compound having a photoreactive group that undergoes at least one of dimerization and isomerization by the action of light. It is also preferable that the photoreactive group has a skeleton of at least one derivative or compound selected from the group consisting of cinnamic acid derivatives, coumarin derivatives, chalcone derivatives, maleimide derivatives, azobenzene compounds, polyimide compounds, stilbene compounds, and spiropyran compounds.

[0086] A photo-alignment film formed from the above-mentioned material is irradiated with linearly polarized or non-polarized light to produce a photo-alignment film. In this specification, "irradiation with linearly polarized light" and "irradiation with non-polarized light" are operations for causing a photoreaction in a photoalignment material. The wavelength of the light used varies depending on the photoalignment material used, and is not particularly limited as long as it is a wavelength necessary for the photoreaction. The peak wavelength of the light used for photoirradiation is preferably 200 nm to 700 nm, and more preferably ultraviolet light with a peak wavelength of 400 nm or less.

[0087] Examples of light sources used for light irradiation include commonly used light sources, such as lamps such as tungsten lamps, halogen lamps, xenon lamps, xenon flash lamps, mercury lamps, mercury xenon lamps, and carbon arc lamps, various lasers [e.g., semiconductor lasers, helium-neon lasers, argon ion lasers, helium cadmium lasers, and YAG (yttrium-aluminum-garnet) lasers], light-emitting diodes, and cathode ray tubes.

[0088] As a means for obtaining linearly polarized light, a method using a polarizing plate (e.g., an iodine polarizing plate, a dichroic dye polarizing plate, and a wire grid polarizing plate), a method using a prism-based element (e.g., a Glan-Thompson prism) or a reflective polarizer using the Brewster angle, or a method using light emitted from a polarized laser light source can be adopted. Also, a filter or a wavelength conversion element may be used to selectively irradiate only light of a required wavelength.

[0089] In the case of linearly polarized light, the light is irradiated from the top or back surface of the alignment film perpendicularly or obliquely to the alignment film surface. The incident angle of the light varies depending on the photoalignment material, but is preferably 0 to 90° (perpendicular), and more preferably 40 to 90°. In the case of non-polarized light, the alignment film is irradiated with non-polarized light obliquely, preferably at an incident angle of 10 to 80°, more preferably at an incident angle of 20 to 60°, and even more preferably at an incident angle of 30 to 50°. The irradiation time is preferably from 1 minute to 60 minutes, and more preferably from 1 minute to 10 minutes.

[0090] When patterning is required, a method of irradiating light using a photomask the number of times required to form a pattern, or a method of writing a pattern by laser light scanning can be used.

[0091] [Adhesive layer] The laminate of the present invention may have an adhesive layer on the opposite side of the transparent resin layer to the optically absorptive anisotropic film, since another functional layer (e.g., the λ / 4 plate described below) is bonded to the opposite side of the transparent resin layer to the optically absorptive anisotropic film. In this specification, the term "adhesive layer" includes the concept of "adhesive layer". Here, "adhesion" is a type of adhesion, and means that the adhesive strength (adhesive strength) changes little even after a certain period of time has passed since the adhesive is applied to the adherend, and the adhesive can be peeled off as needed. In addition, "adhesion" includes the above-mentioned "adhesion" and simply means that the objects to be attached are attached to each other in a unified state.

[0092] The adhesive layer preferably contains a pressure-sensitive adhesive, such as a rubber-based pressure-sensitive adhesive, a (meth)acrylic-based pressure-sensitive adhesive, a silicone-based pressure-sensitive adhesive, a urethane-based pressure-sensitive adhesive, a vinyl alkyl ether-based pressure-sensitive adhesive, a polyvinyl alcohol-based pressure-sensitive adhesive, a polyvinyl pyrrolidone-based pressure-sensitive adhesive, a polyacrylamide-based pressure-sensitive adhesive, or a cellulose-based pressure-sensitive adhesive. Among these, from the viewpoints of transparency, weather resistance, heat resistance, and the like, acrylic adhesives (pressure-sensitive adhesives) are preferred.

[0093] The adhesive layer may contain an antistatic agent. The antistatic agent is likely to diffuse into the light absorption anisotropic film and cause a decrease in the degree of orientation of the dichroic material when exposed to high temperatures and when exposed to moist heat. In response to such problems, the laminate of the present invention having a transparent resin layer can maintain excellent orientation of the dichroic material even when exposed to high temperatures and when exposed to moist heat. In other words, when the laminate of the present invention has an adhesive layer containing an antistatic agent, the effect of the present invention is more pronounced. The antistatic agent may be a compound having an organic cation or a compound having an inorganic cation. The compound having an organic cation may be, for example, the ionic compound described in paragraphs

[0067] to

[0077] of JP-T-2011-504537. The compound having an inorganic cation may be, for example, the metal salt described in paragraphs

[0045] to

[0046] of JP-T-2008-517137. The content of the antistatic agent is preferably from 0.1 to 5 mass %, more preferably from 0.3 to 3 mass %, based on the total mass of all solid contents in the adhesive layer.

[0094] The adhesive layer can be formed, for example, by a method in which a solution of an adhesive (adhesive composition) is applied onto a release sheet, dried, and then transferred to the surface of a transparent resin layer; or a method in which a solution of an adhesive is applied directly onto the surface of a transparent resin layer and dried; or the like. The adhesive solution (adhesive composition) is prepared as a solution of about 10 to 40 mass % by dissolving or dispersing the adhesive in a solvent such as toluene or ethyl acetate. Examples of the coating method that can be used include roll coating methods such as reverse coating and gravure coating, spin coating, screen coating, fountain coating, dipping, and spraying. The adhesive composition may contain the above-mentioned antistatic agent, and may also contain other components (for example, a curing agent, a coupling agent, etc.).

[0095] Examples of materials constituting the release sheet include suitable thin sheets such as synthetic resin films, such as polyethylene, polypropylene, and polyethylene terephthalate; rubber sheets; paper; cloth; nonwoven fabrics; nets; foam sheets; and metal foils.

[0096] In the present invention, the thickness of the optional adhesive layer is not particularly limited, but is preferably from 3 to 50 μm, more preferably from 4 to 40 μm, and particularly preferably from 5 to 30 μm.

[0097] [λ / 4 plate] The laminate of the present invention may have a λ / 4 plate on the side of the adhesive layer opposite to the transparent resin layer side. Here, the term "λ / 4 plate" refers to a plate having a λ / 4 function, specifically, a plate having the function of converting linearly polarized light of a certain wavelength into circularly polarized light (or circularly polarized light into linearly polarized light). A specific example of a λ / 4 plate is described in, for example, US Patent Application Publication No. 2015 / 0277006. For example, specific examples of the λ / 4 plate having a single layer structure include a stretched polymer film and a retardation film having an optically anisotropic layer having λ / 4 function provided on a support, and specific examples of the λ / 4 plate having a multilayer structure include a broadband λ / 4 plate formed by laminating a λ / 4 plate and a λ / 2 plate.

[0098] [Application] The laminate of the present invention can be used as a polarizing element (polarizing plate), specifically, for example, as a linear polarizing plate or a circular polarizing plate. When the laminate of the present invention does not have an optically anisotropic layer such as the λ / 4 plate, the laminate can be used as a linear polarizing plate. On the other hand, when the laminate of the present invention has the λ / 4 plate, the laminate can be used as a circular polarizing plate.

[0099] [Method of manufacturing laminate] The method for producing a laminate of the present invention is a method for producing the laminate of the present invention described above. The method for producing the laminate of the present invention includes a light absorption anisotropic film-forming step of forming a light absorption anisotropic film on the transparent support using a composition containing the dichroic substance represented by the above formula (1) (specific dichroic substance); The method includes a transparent resin layer formation step of forming a transparent resin layer on the light absorption anisotropic film using a curable composition containing the above-mentioned particles and at least one of the above-mentioned polymerizable compound and a polymer obtained by polymerizing the above-mentioned polymerizable compound.

[0100] [Light absorption anisotropic film forming process] The optically absorptive anisotropic film forming process is a process of forming an optically absorptive anisotropic film on the above-mentioned transparent support using a composition containing the dichroic substance (specific dichroic substance) represented by the above-mentioned formula (1). Here, the composition is preferably a liquid crystal composition as explained in the optically absorptive anisotropic film included in the laminate of the present invention. In addition, examples of a method for forming an optically absorptive anisotropic film using the composition include the same formation method as described for the optically absorptive anisotropic film contained in the laminate of the present invention, i.e., a formation method having the above-mentioned coating film formation step and orientation step.

[0101] [Transparent resin layer formation process] The transparent resin layer forming step is a step of forming a transparent resin layer, which is included in the laminate of the present invention, on the optically absorptive anisotropic film described above by using the curable composition described above. Moreover, examples of a method for forming a transparent resin layer using the curable composition include the same methods as those described for the transparent resin layer of the laminate of the present invention.

[0102] [Image display device] The image display device of the present invention comprises the above-mentioned laminate of the present invention, and a display element disposed on the opposite side of the transparent resin layer of the above-mentioned laminate to the optically absorptive anisotropic film side. The display element used in the image display device of the present invention is not particularly limited, and examples thereof include a liquid crystal cell, an organic electroluminescence (hereinafter abbreviated as "EL") display panel, and a plasma display panel. Among these, a liquid crystal cell or an organic EL display panel is preferred, and a liquid crystal cell is more preferred. That is, the image display device of the present invention is preferably a liquid crystal display device using a liquid crystal cell as a display element, or an organic EL display device using an organic EL display panel as a display element, and more preferably a liquid crystal display device.

[0103] [Liquid crystal display device] A liquid crystal display device, which is one example of the image display device of the present invention, is a liquid crystal display device having the above-mentioned laminate of the present invention (however, not including a λ / 4 plate) and a liquid crystal cell. In the present invention, of the laminates provided on both sides of the liquid crystal cell, it is preferable to use the laminate of the present invention as the front side polarizing element, and it is more preferable to use the laminate of the present invention as the front side and rear side polarizing elements. The liquid crystal cell constituting the liquid crystal display device will be described in detail below.

[0104] <Liquid crystal cell> The liquid crystal cell used in the liquid crystal display device is preferably in VA (Vertical Alignment) mode, OCB (Optically Compensated Bend) mode, IPS (In-Plane-Switching) mode, or TN (Twisted Nematic) mode, but is not limited to these. In a TN mode liquid crystal cell, rod-shaped liquid crystal molecules are aligned substantially horizontally when no voltage is applied, and are further aligned in a twisted manner at an angle of 60 to 120°. TN mode liquid crystal cells are most commonly used as color TFT (Thin Film Transistor) liquid crystal display devices, and are described in many publications. In a VA mode liquid crystal cell, rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied. VA mode liquid crystal cells include (1) a narrow-sense VA mode liquid crystal cell (described in JP-A-2-176625) in which rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied and substantially horizontally when voltage is applied, (2) a VA mode multi-domain (MVA mode) liquid crystal cell (described in SID97, Digest of tech. Papers (Proceedings) 28 (1997) 845) in order to expand the viewing angle, (3) a mode (n-ASM mode) liquid crystal cell in which rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied and are aligned in a twisted multi-domain when voltage is applied (described in Proceedings of the Japan Liquid Crystal Discussion Society 58-59 (1998)), and (4) a SURVIVAL mode liquid crystal cell (announced at LCD International 98). In addition, the liquid crystal display may be of any of a PVA (Patterned Vertical Alignment) type, an optical alignment type, and a PSA (Polymer-Sustained Alignment) type. Details of these modes are described in JP-A-2006-215326 and JP-A-2008-538819. In the IPS mode liquid crystal cell, rod-shaped liquid crystal molecules are aligned substantially parallel to the substrate, and the liquid crystal molecules respond in a planar manner when an electric field parallel to the substrate surface is applied. In the IPS mode, the black display is achieved when no electric field is applied, and the absorption axes of the pair of upper and lower polarizing plates are perpendicular to each other. Methods of reducing light leakage during black display in an oblique direction and improving the viewing angle using an optical compensation sheet are disclosed in JP-A-10-54982, JP-A-11-202323, JP-A-9-292522, JP-A-11-133408, JP-A-11-305217, JP-A-10-307291, and the like.

[0105] [Organic EL display device] An organic EL display device, which is one example of the image display device of the present invention, preferably has, from the viewing side, the above-mentioned laminate of the present invention (including a transparent support, an alignment film, an adhesive layer, and a λ / 4 plate) and an organic EL display panel. In this case, the laminate is arranged in the order of the transparent support, the alignment film, the light absorption anisotropic film, the transparent resin layer, the adhesive layer, and the λ / 4 plate from the viewing side. The organic EL display panel is a display panel configured using an organic EL element having an organic light-emitting layer (organic electroluminescence layer) sandwiched between electrodes (cathode and anode). The configuration of the organic EL display panel is not particularly limited, and a known configuration may be adopted. EXAMPLES

[0106] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0107] [Example 1] <Preparation of Transparent Support 1> An alignment film coating solution having the following composition was continuously applied onto a 40 μm-thick TAC substrate (TG40, manufactured by Fujifilm Corporation) using a #8 wire bar. After that, it was dried for 2 minutes with hot air at 100° C., thereby obtaining a transparent support 1 in which a 0.8 μm-thick polyvinyl alcohol (PVA) alignment film was formed on the TAC substrate. The modified polyvinyl alcohol was added to the alignment film coating solution so that the solid content concentration was 4 wt %. ---------------------------------------------------------------------------------- Composition of alignment film coating solution ---------------------------------------------------------------------------------- The following modified polyvinyl alcohols 70 parts by mass of water Methanol 30 parts by weight ----------------------------------------------------------------------------------

[0108] Modified Polyvinyl Alcohol [ka]

[0109] <Formation of alignment film 1> To 1 part by mass of photoalignment material E-1 having the following structure, 41.6 parts by mass of butoxyethanol, 41.6 parts by mass of dipropylene glycol monomethyl, and 15.8 parts by mass of pure water were added, and the resulting solution was pressure-filtered through a 0.45 μm membrane filter to prepare composition 1 for forming an alignment film. Next, the obtained composition 1 for forming an alignment film was applied onto a transparent support 1 and dried at 60° C. for 1 minute. Thereafter, the obtained coating film was irradiated with linearly polarized ultraviolet light (illuminance 4.5 mW, irradiation amount 500 mJ / cm 2 ) using a polarized ultraviolet light exposure device. 2 ) was irradiated to prepare an alignment film 1 (referred to as azo (E-1) in Table 1 below).

[0110] [ka]

[0111] <Formation of optically absorbing anisotropic film 1> Onto the obtained alignment film 1, the following liquid crystal composition 1 (abbreviated as “composition 1” in the following Table 1) was continuously applied with a #4 wire bar to form a coating film 1. Next, the coating film 1 was heated at 140° C. for 90 seconds, and then cooled to room temperature (23° C.). It was then heated at 80° C. for 60 seconds and cooled again to room temperature. Then, a high-pressure mercury lamp was used to illuminate the area at an intensity of 28 mW / cm 2 By irradiating the film for 60 seconds under the irradiation conditions, an optically absorptive anisotropic film 1 was formed on the alignment film 1. ------------------------------------------------------------------ Composition of Liquid Crystal Composition 1 ------------------------------------------------------------------ Yellow azo dye Y-1 (0.23 parts by weight) 0.21 parts by weight of the following magenta azo dye M-1 0.46 parts by weight of the following cyan azo dye C-1 4.03 parts by weight of the following polymeric liquid crystal compound P-1 Antioxidant Irganox 1076 (BASF) 0.034 parts by mass Polymerization initiator IRGACURE819 (BASF) 0.043 parts by mass 0.039 parts by mass of the following interface improver F-1 Cyclopentanone 66.50 parts by mass Tetrahydrofuran 28.50 parts by mass ------------------------------------------------------------------

[0112] Yellow azo dye Y-1 [ka]

[0113] Magenta azo dye Y-1 [ka]

[0114] Cyan azo dye C-1 [ka]

[0115] Polymer liquid crystal compound P-1 [ka]

[0116] Antioxidant Irganox1076 [ka]

[0117] Interface improver F-1 [ka]

[0118] [Examples 2 and 3] Laminates of Examples 2 and 3 were obtained in the same manner as in Example 1, except that in the formation of the optically absorptive anisotropic film, the liquid crystal composition 1 was changed to the following liquid crystal compositions 2 and 3. ------------------------------------------------------------------ Composition of Liquid Crystal Composition 2 ------------------------------------------------------------------ Yellow azo dye Y-1 (0.13 parts by weight) 0.21 parts by mass of the following magenta azo dye M-2 0.56 parts by weight of the following cyan azo dye C-2 4.03 parts by mass of the following polymeric liquid crystal compound P-2 Antioxidant Irganox 1076 (BASF) 0.034 parts by mass Polymerization initiator IRGACURE819 (BASF) 0.043 parts by mass 0.039 parts by mass of the following interface improver F-1 Cyclopentanone 66.50 parts by mass Tetrahydrofuran 28.50 parts by mass ------------------------------------------------------------------

[0119] Yellow azo dye Y-1 [ka]

[0120] Magenta azo dye M-2 [ka]

[0121] Cyan azo dye C-2 [ka]

[0122] Polymer liquid crystal compound P-2 [ka]

[0123] ------------------------------------------------------------------ Composition of Liquid Crystal Composition 3 ------------------------------------------------------------------ Yellow azo dye Y-2 (0.23 parts by weight) 0.21 parts by weight of the following magenta azo dye M-3 0.46 parts by weight of the following cyan azo dye C-3 4.03 parts by mass of the following polymeric liquid crystal compound P-2 Antioxidant Irganox 1076 (BASF) 0.034 parts by mass Polymerization initiator IRGACURE819 (BASF) 0.043 parts by mass 0.039 parts by mass of the following interface improver F-1 Cyclopentanone 66.50 parts by mass Tetrahydrofuran 28.50 parts by mass ------------------------------------------------------------------

[0124] Yellow azo dye Y-2 [ka]

[0125] Magenta azo dye M-3 [ka]

[0126] Cyan azo dye C-3 [ka]

[0127] [Examples 4 to 10] In the formation of the light absorbing anisotropic film, the liquid crystal composition was prepared in the same manner as in Example 2, except that the antioxidant Irganox1076 was changed to various antioxidants and the amounts added were as shown in Table 1 below. The laminates of Examples 4 to 10 were obtained in the same manner as in Example 2, except that the above compositions were used. The structures of various antioxidants used in forming the optically absorptive anisotropic films in Examples 4 to 10 are shown below.

[0128] ADEKA STAB LA-77 (made by ADEKA) [ka]

[0129] Irgafos168 (manufactured by BASF) [ka]

[0130] SumilizerGM (Sumitomo Chemical Co., Ltd.) [ka]

[0131] Compound A [ka]

[0132] [Synthesis of Compound A] [ka]

[0133] Dibutylhydroxytoluene (BHT) (200 mg) was added to a tetrahydrofuran (THF) solution (70 mL) of methanesulfonyl chloride (MsCl) (73.4 mmol, 5.7 mL), and the internal temperature was cooled to -5° C. A THF solution of 1,8-octanedicarboxylic acid (33.3 mmol, 6.75 g) and diisopropylethylamine (DIPEA) (75.6 mmol, 13.0 mL) was added dropwise thereto so that the internal temperature did not rise above 0° C. After stirring at -5°C for 30 minutes, N,N-dimethyl-4-aminopyridine (DMAP) (200mg) was added, and diisopropylethylamine (75.6mmol, 13.0mL) and a solution of 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical (60.6mmol, 10.4g) in tetrahydrofuran (THF) and dimethylacetamide (DMAc) were added dropwise so that the internal temperature did not rise above 0°C. Then, the mixture was stirred at room temperature for 4 hours. After adding methanol (5mL) to stop the reaction, water and ethyl acetate were added. The organic layer extracted with ethyl acetate was subjected to solvent removal using a rotary evaporator, and the mixture was purified by column chromatography using ethyl acetate and hexane to obtain 10.2g (yield 60%) of compound A as a white solid.

[0134] [Example 11] <Synthesis of Liquid Crystal Compounds> A liquid crystal compound (1-6) represented by the following formula (1-6) was synthesized according to the method described in Lub et al. Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996). [ka]

[0135] Next, a liquid crystal compound (1-7) represented by the following formula (1-7) was synthesized with reference to the synthesis method of the above compound (1-6). [ka]

[0136] <Preparation of Liquid Crystal Composition 11> The following components were mixed and stirred at 80° C. for 1 hour to prepare liquid crystal composition 11 (abbreviated as “composition 11” in Table 1 below).

[0137] ---------------------------------------------------------------------------------- Composition of Liquid Crystal Composition 11 ---------------------------------------------------------------------------------- Liquid crystal compound (1-6) 50 parts by mass Liquid crystal compound (1-7) 50 parts by mass Azo dye (G-205; Hayashibara Biochemical Laboratory) 2.5 parts by weight Compound A 0.2 parts by mass Polymerization initiator Irgacure 369 (BASF) 6 parts by weight Polyacrylate Compounds (BYK-361N; manufactured by BYK-Chemie) 1.2 parts by weight Cyclopentanone 250 parts by mass ----------------------------------------------------------------------------------

[0138] A laminate of Example 10 was obtained in the same manner as in Example 1, except that the liquid crystal composition 1 was changed to the liquid crystal composition 11 and an optically absorptive anisotropic film was formed according to the formation method described below.

[0139] <Formation method> On the alignment film 1, the liquid crystal composition 2 was applied by spin coating so as to have a film thickness of 0.7 μm. Thereafter, the liquid crystal composition 2 was dried by heating on a hot plate at 120° C. for 3 minutes, and then promptly cooled to 70° C. or less. Then, the liquid crystal composition 2 was exposed to light at a dose of 2400 mJ / cm 2 using an ultraviolet irradiation device. 2 (365 nm standard) was irradiated and cured.

[0140] [Example 12] On the optically absorptive anisotropic film of Example 7, the following composition 1 for forming a transparent resin layer was continuously applied with a #2 wire bar, and dried at 40° C. for 90 seconds. After that, a high-pressure mercury lamp was used to illuminate the area at an intensity of 30 mW / cm 2 The resin composition was cured by irradiation under the irradiation conditions of for 10 seconds, to prepare a laminate in which a transparent resin layer A was formed on the optically absorptive anisotropic film.

[0141] ------------------------------------------------------------------ Composition A for forming transparent resin layer ------------------------------------------------------------------ DPHA: Dipentaerythritol hexaacrylate 29 parts by weight Polymerization initiator IRGACURE819 (BASF) 1 part by weight Ethanol 70 parts by weight ------------------------------------------------------------------

[0142] Dipentaerythritol Hexaacrylate [ka]

[0143] [Examples 13-14] Laminates of Examples 13 and 14 were obtained in the same manner as in Example 12, except that in forming the transparent resin layer, composition A for forming a transparent resin layer was changed to compositions B and C for forming a transparent resin layer shown below.

[0144] ------------------------------------------------------------------ Composition B for forming transparent resin layer ------------------------------------------------------------------ 144 parts by weight of CEL2021P (manufactured by Daicel Corporation) -3 parts by weight of IRGACURE127 (BASF) 6 parts by weight of CPI-100P (propylene carbonate solution) Megafac RS-90 (DIC) 0.3 parts by weight Methyl ethyl ketone (MEK) 347 parts by weight ------------------------------------------------------------------

[0145] CEL2021P [ka]

[0146] IRGACURE127 [ka]

[0147] Photo-induced cationic polymerization initiator (CPI-100P) [ka]

[0148] ------------------------------------------------------------------ Composition C for forming transparent resin layer ------------------------------------------------------------------ 54 parts by weight of CEL2021P (manufactured by Daicel Corporation) IRGACURE127 (BASF) 3 parts by weight 3 parts by weight of the above CPI-100P (propylene carbonate solution) Organosilica sol MEK-EC-2130Y (Nissan Chemical) 300 parts by mass Megafac RS-90 (DIC) 7.5 parts by weight Methyl ethyl ketone (MEK) 133 parts by weight ------------------------------------------------------------------

[0149] [Example 15] <Formation of alignment film 2> (Synthesis of Polymer E-2) In a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel and a reflux condenser, 100.0 parts by mass of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 500 parts by mass of methyl isobutyl ketone and 10.0 parts by mass of triethylamine were charged, and the mixture was stirred at room temperature. Next, 100 parts by mass of deionized water was dropped into the mixture obtained from the dropping funnel over 30 minutes, and then the mixture was mixed under reflux and reacted at 80°C for 6 hours. After the reaction was completed, the organic phase was taken out and washed with a 0.2% by mass aqueous solution of ammonium nitrate until the water after washing was neutral. Then, the solvent and water were distilled off from the obtained organic phase under reduced pressure, and polyorganosiloxane having epoxy groups was obtained as a viscous transparent liquid. Regarding this polyorganosiloxane having an epoxy group, 1 H-NMR (Nuclear Magnetic Resonance) analysis showed that the peak due to the oxiranyl group was obtained at a chemical shift (δ) of about 3.2 ppm, as expected from the theoretical intensity, and it was confirmed that no side reaction of the epoxy group occurred during the reaction. The weight-average molecular weight Mw of this polyorganosiloxane having epoxy groups was 2,200, and the epoxy equivalent was 186 g / mol. Next, 10.1 parts by mass of the polyorganosiloxane having an epoxy group obtained above, 0.5 parts by mass of an acrylic group-containing carboxylic acid (Toa Gosei Co., Ltd., product name "Aronix M-5300", acrylic acid ω-carboxy polycaprolactone (polymerization degree n ≒ 2)), 20 parts by mass of butyl acetate, 1.5 parts by mass of a cinnamic acid derivative obtained by the method of Synthesis Example 1 of JP 2015-26050 A, and 0.3 parts by mass of tetrabutylammonium bromide were charged into a 100 mL three-neck flask, and the resulting mixture was stirred at 90 ° C. for 12 hours. After stirring, the mixture was diluted with an equal amount (by mass) of butyl acetate to the obtained mixture, and the diluted mixture was washed with water three times. The operation of concentrating the obtained mixture and diluting it with butyl acetate was repeated twice, and finally, a solution containing a polyorganosiloxane having a photoalignable group (polymer E-2 below) was obtained. The weight average molecular weight Mw of this polymer E-2 was 9,000. In addition, 1As a result of 1 H-NMR analysis, the content of components having cinnamate groups in polymer E-2 was 23.7% by mass.

[0150] [ka]

[0151] (Preparation of composition 2 for forming alignment film) The following components were mixed to prepare an alignment film-forming composition 2. ------------------------------------------------------------------ Composition of composition 2 for forming alignment film ------------------------------------------------------------------ The above polymer E-2: 10.67 parts by mass 5.17 parts by mass of the following low molecular weight compound R-1 0.53 parts by mass of the following additive (B-1) Butyl acetate 8287.37 parts by mass Propylene glycol monomethyl ether acetate 2071.85 parts by mass ------------------------------------------------------------------

[0152] [ka]

[0153] Additive (B-1): TA-60B manufactured by San-Apro Co., Ltd. (see structural formula below) [ka]

[0154] Composition 2 for forming an alignment film was applied onto a TAC support by spin coating, and the support onto which composition 2 for forming an alignment film was applied was dried on a hot plate at 80°C for 5 minutes to remove the solvent and form a coating film. The resulting coating was irradiated with polarized UV light (25 mJ / cm 2, an ultra-high pressure mercury lamp) to prepare an alignment film 2 (referred to as cinnamoyl (E-2) in Table 1 below).

[0155] A laminate of Example 15 was obtained in the same manner as in Example 1, except that the alignment film 2 was used instead of the alignment film 1.

[0156] [Example 16] <Formation of Orientation Film 3> The composition 3 for forming an alignment film was applied onto the dried PET support using a #4 bar, and the applied composition 3 for forming an alignment film was dried at 80°C for 15 minutes and then heated at 250°C for 1 hour to form a coating film on the PET support. The resulting coating film was irradiated with polarized ultraviolet light (1 J / cm 2 An alignment film 3 (referred to as polyimide in Table 1 below) was prepared on the PET support by irradiating the PET support once with a light source (such as a super-high pressure mercury lamp).

[0157] ------------------------------------------------------------------ Composition of composition 3 for forming alignment film ------------------------------------------------------------------ Polyimide alignment film material (SE-130, Nissan Chemical Co., Ltd.) 2.0 parts by weight N-Methylpyrrolidone 98.0 parts by mass ------------------------------------------------------------------

[0158] A laminate of Example 16 was obtained in the same manner as in Example 1, except that the alignment film 3 was used instead of the alignment film 1.

[0159] [Comparative Examples 1 and 2] The laminates of Comparative Examples 1 and 2 were prepared in the same manner as in Example 1, except that the liquid crystal composition 1 was changed to the following liquid crystal compositions 12 and 13, respectively. ------------------------------------------------------------------ Composition of Liquid Crystal Composition 12 ------------------------------------------------------------------ 0.13 parts by mass of the above yellow azo dye Y-1 0.21 parts by mass of the above magenta azo dye M-1 0.56 parts by mass of the above cyan azo dye C-1 The above polymer liquid crystal compound P-1: 4.03 parts by mass Polymerization initiator IRGACURE819 (BASF) 0.043 parts by mass 0.039 parts by mass of the following interface improver F-1 Cyclopentanone 66.50 parts by mass Tetrahydrofuran 28.50 parts by mass ------------------------------------------------------------------

[0160] ------------------------------------------------------------------ Composition of Liquid Crystal Composition 13 ------------------------------------------------------------------ Liquid crystal compound (1-6) 50 parts by mass Liquid crystal compound (1-7) 50 parts by mass Azo dye (G-205; Hayashibara Biochemical Laboratory) 2.5 parts by weight Polymerization initiator Irgacure 369 (BASF) 6 parts by weight Polyacrylate Compounds (BYK-361N; manufactured by BYK-Chemie) 1.2 parts by weight Cyclopentanone 250 parts by mass ------------------------------------------------------------------

[0161] <Orientation degree> With a linear polarizer inserted on the light source side of an optical microscope (Nikon Corporation, product name "ECLIPSE E600 POL"), the laminates of the examples and comparative examples were set on the sample stage, and the absorbance of the laminates in the wavelength range of 400 to 700 nm was measured using a multichannel spectrometer (Ocean Optics, product name "QE65000"), and the degree of orientation was calculated using the following formula. The results are shown in Table 1 below. Orientation degree: S=[(Az0 / Ay0)-1] / [(Az0 / Ay0)+2] Az0: Absorbance of the laminate with respect to polarized light in the absorption axis direction Ay0: absorbance of the laminate with respect to polarized light in the direction of the polarization axis

[0162] <Light resistance> The laminate thus produced was placed in a light resistance tester (manufactured by Suga Test Instruments, product name "Xenon Weather Meter X25") with the adhesive layer and glass attached to the surface of the transparent resin layer, and the glass substrate was irradiated with light from a xenon lamp light source at 200,000 lux for 100 hours (equivalent to an accumulated light quantity of 20 million lux·h). The transmittance was measured before and after this test, and evaluated according to the following criteria. The results are shown in Table 1 below. 7: Transmittance change is less than 0.2% 6: Transmittance change is 0.2% or more but less than 0.5% 5: Transmittance change is 0.5% or more but less than 1.0% 4: Transmittance change is 1.0% or more but less than 1.5% 3: Transmittance change is 1.5% or more but less than 3.0% 2: Transmittance change is 3.0% or more and less than 5.0% 1: Transmittance change is 5.0% or more

[0163] [Table 1]

[0164] In Table 1, the term "ratio to dye" means the molar ratio of the antioxidant to the content (mol) of the liquid crystal compound P-1 in the liquid crystal composition.

[0165] The evaluation results in Table 1 show that the optically absorptive anisotropic film containing a dichroic material and an antioxidant, and the laminate in which a transparent resin layer is adjacent to the optically absorptive anisotropic film, maintain excellent orientation of the dichroic material and exhibit good light resistance.

[0166] [Example 28] [Preparation of λ / 4 Retardation Film 1] <Preparation of composition for photoalignment film> A composition similar to the composition 2 for forming an alignment film used in forming the alignment film 2 used in Example 20 was prepared.

[0167] <Preparation of Coating Solution for Optically Anisotropic Layer> A coating solution for an optically anisotropic layer having the following composition was prepared. ------------------------------------------------------------------ Coating solution for optically anisotropic layer ------------------------------------------------------------------ The following liquid crystal compound L-3: 42.00 parts by mass The following liquid crystal compound L-4: 42.00 parts by mass The following polymerizable compound A-1: ​​16.00 parts by mass 6.00 parts by mass of the following low molecular weight compound B-2 0.50 parts by mass of the following polymerization initiator S-1 (oxime type) Leveling agent G-1 (listed below): 0.20 parts by weight 2.00 parts by mass of HYSOLV MTEM (manufactured by Toho Chemical Industry Co., Ltd.) NK Ester A-200 (manufactured by Shin-Nakamura Chemical Co., Ltd.) 1.00 parts by mass Methyl ethyl ketone 424.8 parts by mass ------------------------------------------------------------------ In addition, the group adjacent to the acryloyloxy group in the following liquid crystal compounds L-3 and L-4 represents a propylene group (a group in which a methyl group is replaced with an ethylene group), and the following liquid crystal compounds L-3 and L-4 represent a mixture of positional isomers in which the position of the methyl group is different.

[0168] [ka] JPEG0007602597000043.jpg2296 JPEG0007602597000044.jpg1853 JPEG0007602597000045.jpg2482 JPEG0007602597000046.jpg2387

[0169] [Preparation of Cellulose Acylate Film 1] (Preparation of Core Layer Cellulose Acylate Dope) The following composition was charged into a mixing tank and stirred to dissolve each component, thereby preparing a cellulose acetate solution to be used as a cellulose acylate dope for the core layer. ───────────────────────────────── Core layer: Cellulose acylate dope ───────────────────────────────── Cellulose acetate with an acetyl substitution degree of 2.88 100 parts by mass In the embodiment of JP 2015-227955 A 12 parts by weight of the polyester compound B Compound F below: 2 parts by weight Methylene chloride (first solvent) 430 parts by mass Methanol (second solvent) 64 parts by weight ─────────────────────────────────

[0170] Compound F [ka]

[0171] (Preparation of outer layer cellulose acylate dope) To 90 parts by weight of the above-mentioned cellulose acylate dope for the core layer, 10 parts by weight of the following matting agent solution was added to prepare a cellulose acetate solution to be used as the cellulose acylate dope for the outer layer. ───────────────────────────────── Matting agent solution ───────────────────────────────── Silica particles with an average particle size of 20 nm (AEROSIL R972, manufactured by Nippon Aerosil Co., Ltd.) 2 parts by weight Methylene chloride (first solvent) 76 parts by mass Methanol (second solvent) 11 parts by weight 1 part by weight of the above-mentioned cellulose acylate dope for the core layer ─────────────────────────────────

[0172] (Preparation of Cellulose Acylate Film 1) The above core layer cellulose acylate dope and the above outer layer cellulose acylate dope were filtered through a filter paper with an average pore size of 34 μm and a sintered metal filter with an average pore size of 10 μm, and then the above core layer cellulose acylate dope and the outer layer cellulose acylate dope on both sides were simultaneously cast onto a drum at 20°C from a casting nozzle (band casting machine). Next, the film was peeled off while the solvent content was about 20% by mass, and both ends in the width direction of the film were fixed with tenter clips, and the film was stretched in the transverse direction at a stretch ratio of 1.1 times while being dried. Thereafter, the film was further dried by conveying it between rolls of a heat treatment device to prepare a 40 μm-thick cellulose acylate film 1. The in-plane retardation of the obtained cellulose acylate film 1 was 0 nm.

[0173] [Preparation of λ / 4 Retardation Film 1] Each of the compositions for photoalignment films prepared above was applied to one side of the prepared cellulose acylate film 1 using a bar coater. After coating, the coating was dried on a hot plate at 120° C. for 1 minute to remove the solvent, thereby forming a photoisomerizable composition layer having a thickness of 0.3 μm. The obtained photoisomerizable composition layer was irradiated with polarized ultraviolet light (10 mJ / cm 2 A photo-alignment film was formed by irradiating the liquid crystal with a liquid crystal display (using an ultra-high pressure mercury lamp). Next, the coating liquid for the optically anisotropic layer previously prepared was applied onto the photoalignment film with a bar coater to form a composition layer. The formed composition layer was heated to 110° C. on a hot plate and then cooled to 60° C. to stabilize the orientation. After that, the temperature was kept at 60°C and the specimen was irradiated with ultraviolet light (500 mJ / cm) in a nitrogen atmosphere (oxygen concentration 100 ppm). 2 The orientation was fixed by irradiation with a super-high pressure mercury lamp) to form an optically anisotropic layer having a thickness of 2.3 μm, thereby producing λ / 4 phase difference film 1. The in-plane retardation of the obtained optical laminate was 140 nm.

[0174] [Preparation of positive C-plate film 2] A commercially available triacetyl cellulose film "Z-TAC" (manufactured by Fujifilm Corporation) was used as a temporary support (this film is referred to as cellulose acylate film 2). Cellulose acylate film 2 was passed through a dielectric heating roll at a temperature of 60°C to raise the film surface temperature to 40°C, and then an alkaline solution having the composition shown below was applied to one side of the film using a bar coater in an amount of 14 ml / m. 2 The mixture was heated to 110° C. and conveyed under a steam type far-infrared heater manufactured by Noritake Co., Ltd. for 10 seconds. Next, using the same bar coater, pure water was applied at 3 ml / m 2 It was applied. Next, after repeating washing with a fountain coater and draining with an air knife three times, the film was transported to a drying zone at 70° C. for 10 seconds and dried to prepare an alkaline saponified cellulose acylate film 2. ───────────────────────────────── Composition of alkaline solution (parts by weight) ───────────────────────────────── Potassium hydroxide 4.7 parts by mass Water 15.8 parts by mass Isopropanol 63.7 parts by weight Fluorine-containing surfactant SF-1 (C 14 H 29 O(CH2CH 2O ) 20 H) 1.0 parts by mass Propylene glycol 14.8 parts by weight ─────────────────────────────────

[0175] The above-mentioned alkaline saponified cellulose acylate film 2 was continuously coated with a coating solution for forming an alignment layer having the following composition using a wire bar #8. The film was dried with hot air at 60° C. for 60 seconds and then with hot air at 100° C. for 120 seconds to form an alignment layer. ───────────────────────────────── Composition of coating solution for forming alignment film ───────────────────────────────── PVA (manufactured by Kuraray, product name "Kuraray Poval PVA-103") 2.4 parts by mass Isopropyl alcohol 1.6 parts by weight Methanol 36 parts by weight 60 parts by mass of water ─────────────────────────────────

[0176] The following coating solution N was applied onto the cellulose acylate film 2 having the alignment layer prepared above, and the coating solution was aged at 60° C. for 60 seconds. Then, the coating solution was aged at 70 mW / cm 2 in air. 2 An air-cooled metal halide lamp (manufactured by Eye Graphics Co., Ltd.) was used, producing 1000 mJ / cm 2 The alignment state was fixed by irradiating the polymerizable rod-like liquid crystal compound with ultraviolet light of 1000 nm to vertically align the polymerizable rod-like liquid crystal compound, thereby preparing a positive C plate film 1. The Rth was −60 nm at a wavelength of 550 nm.

[0177] ───────────────────────────────── Composition of coating solution N for optically anisotropic layer ───────────────────────────────── The following liquid crystal compound L-1: 80 parts by weight 20 parts by weight of the following liquid crystal compound L-2 1 part by weight of the following vertical alignment liquid crystal compound activator (S01) Ethylene oxide modified trimethylolpropane triacrylate (V#360, manufactured by Osaka Organic Chemical Co., Ltd.) 8 parts by mass Irgacure 907 (BASF) 3 parts by weight Kayacure DETX (manufactured by Nippon Kayaku Co., Ltd.) 1 part by weight 0.4 parts by mass of the following compound B03 Methyl ethyl ketone 170 parts by mass Cyclohexanone 30 parts by mass ─────────────────────────────────

[0178] [ka] JPEG0007602597000049.jpg4897 JPEG0007602597000050.jpg2468

[0179] <Preparation of circular polarizing plate> The positive C plate film 2 prepared above was transferred to the optically anisotropic layer side of the λ / 4 retardation film 1 via an adhesive, and the cellulose acylate film 2 was removed. In addition, the laminate prepared in Example 1 was attached to the cellulose acylate film 1 side of the λ / 4 retardation film via an adhesive to obtain a circularly polarizing plate.

[0180] A Samsung GALAXY S5 equipped with an organic EL panel (organic EL display element) was disassembled, the touch panel with the circular polarizer was peeled off from the organic EL display device, and the circular polarizer was peeled off from the touch panel to separate the organic EL display element, the touch panel, and the circular polarizer. The separated touch panel was then attached to the organic EL display element again, and the circular polarizer prepared above was attached to the touch panel so that the positive C plate side was on the panel side to prepare an organic EL display device.

[0181] The prepared organic EL display device was evaluated in the same manner as when Pure Ace WR (manufactured by Teijin Limited) was used as the λ / 4 plate, and it was confirmed that the same effect was achieved when a laminate of a λ / 4 phase difference film 1 and a positive C plate film 2 was used as the λ / 4 plate. [Explanation of symbols]

[0182] 10, 20 optical laminate 12 Transparent support 14 Transparent resin layer 16 Photoalignment layer 18 Optically Absorbing Anisotropic Layer

Claims

1. A light absorbing anisotropic film containing a dichroic substance having an azo group and at least one antioxidant, the content of the antioxidant is 1 to 25 mol % based on the total molar mass of the dichroic substances; the antioxidant has at least one of a hindered phenol, a hindered amine (excluding compounds having an N-oxyl structure), a thioether, and a phosphite compound; At least one of the dichroic substances has a structure represented by the following formula (2): The optically absorptive anisotropic film has a dichroic substance having a structure represented by the formula (2) in an amount of 5 to 25% by mass relative to the total mass of the optically absorptive anisotropic film. 【Chemistry 1】 In the formula (2), A 4 represents a divalent aromatic group which may have a substituent. In the formula (2), L 3 and L 4 each independently represents a substituent. In the formula (2), E represents any one of a nitrogen atom, an oxygen atom, and a sulfur atom. In the formula (2), R 1 represents a hydrogen atom, a halogen atom, an alkyl group which may have a substituent, or an alkoxy group which may have a substituent. In the formula (2), R 2 represents a hydrogen atom or an alkyl group which may have a substituent. In the formula (2), R 3 represents a hydrogen atom or a substituent. In the formula (2), n represents 0 or 1. However, when E is a nitrogen atom, n is 1, and when E is an oxygen atom or a sulfur atom, n is 0.

2. In the formula (2), A 4 The optically absorptive anisotropic film according to claim 1 , wherein is a phenylene group.

3. In the formula (2), L 3 and L 4 The optically absorptive anisotropic film according to claim 1 , wherein at least one of the above groups contains a crosslinkable group.

4. In the formula (2), L 3 and L 4 The optically absorptive anisotropic film according to any one of claims 1 to 3, wherein both of the above groups contain a crosslinkable group.

5. 5. The optically absorptive anisotropic film according to claim 3, wherein the crosslinkable group is an acryloyl group or a methacryloyl group.

6. 6. The optically absorptive anisotropic film according to claim 1, further comprising a liquid crystalline compound.

7. A light absorbing anisotropic film according to any one of claims 1 to 6, and a transparent resin layer, A laminate in which the optically absorptive anisotropic film and the transparent resin layer are adjacent to each other.

8. The laminate according to claim 7 , wherein the transparent resin layer is a layer obtained by using a curable composition containing at least one of a polymerizable compound and a polymer obtained by polymerizing the polymerizable compound.

9. The laminate according to claim 7 or 8, wherein the transparent resin layer further contains particles.

10. The laminate according to any one of claims 7 to 9, further comprising a transparent support on the opposite side of the transparent resin layer provided adjacent to the optically absorptive anisotropic film, and an alignment film between the transparent support and the optically absorptive anisotropic film.

11. The alignment film is a photo-alignment film formed using a composition containing a photo-alignment compound, the photoalignment compound is a photosensitive compound having a photoreactive group that undergoes at least one of dimerization and isomerization by the action of light, The laminate according to claim 10, wherein the photoreactive group has a skeleton of at least one derivative or compound selected from the group consisting of cinnamic acid derivatives, coumarin derivatives, chalcone derivatives, maleimide derivatives, azobenzene compounds, polyimide compounds, stilbene compounds, and spiropyran compounds.

12. The laminate according to any one of claims 7 to 11, further comprising an adhesive layer on the opposite side of the transparent resin layer to the optically absorptive anisotropic film.

13. The laminate according to claim 12 , further comprising a λ / 4 plate on the side of the adhesive layer opposite to the transparent resin layer.

14. A method for producing a laminate having an optically absorptive anisotropic film and a transparent resin layer, comprising the steps of: a light absorbing anisotropic film forming step of forming a light absorbing anisotropic film using a composition containing a dichroic substance having an azo group and at least one type of antioxidant; a transparent resin layer forming step of forming a transparent resin layer on the optically absorptive anisotropic film using a curable composition containing at least one of a polymerizable compound and a polymer obtained by polymerizing the polymerizable compound, the content of the antioxidant is 1 to 25 mol % based on the total molar mass of the dichroic substances; the antioxidant has at least one of a hindered phenol, a hindered amine (excluding compounds having an N-oxyl structure), a thioether, and a phosphite compound; At least one of the dichroic substances has a structure represented by the following formula (2): A method for producing a laminate, wherein the content of the dichroic substance having the structure represented by formula (2) is 5 to 25% by mass based on the total mass of the optically absorptive anisotropic film. 【Chemistry 2】 In the formula (2), A 4 represents a divalent aromatic group which may have a substituent. In the formula (2), L 3 and L 4 each independently represents a substituent. In the formula (2), E represents any one of a nitrogen atom, an oxygen atom, and a sulfur atom. In the formula (2), R 1 represents a hydrogen atom, a halogen atom, an alkyl group which may have a substituent, or an alkoxy group which may have a substituent. In the formula (2), R 2 represents a hydrogen atom or an alkyl group which may have a substituent. In the formula (2), R 3 represents a hydrogen atom or a substituent. In the formula (2), n represents 0 or 1. However, when E is a nitrogen atom, n is 1, and when E is an oxygen atom or a sulfur atom, n is 0.

15. 14. An image display device comprising: the laminate according to claim 7; and a display element disposed on a side of the laminate opposite to a light absorption anisotropic film side of the transparent resin layer.

Citation Information

Patent Citations

  • Composition

    JP2016006502A

  • Polymerizable liquid crystal composition, polarizing film and method for manufacturing the same, polarizing plate and display device

    JP2019133148A